Education “Technology” in Heritage Conservation: from Concept to Methodology - a Methodological Mechanism - Lobovikov-Katz, Anna (Technical Annals, 2025)
Heritage education for the general public has been recognized as a crucial component of the contemporary inter- and multi-disciplinary Conservation of Cultural Heritage (CCH(. However, educational methodologies in this area, and specifically those dedicated to education for preservation and conservation of cultural heritage for the general public, are still limited in number. This paper proposes a “technology” in heritage education, and presents a methodological mechanism in this area, which was developed in the first phase of the EU project “Educational Linkage Approach in Cultural Heritage (ELAICH)”, and enabled the project development through its different stages. The paper outlines an intrinsic research mechanism (the Methodological Mechanism of the Educational Approach), through basic “Why,” “What,” and “How" of its structure, development and implementation; and analyses its efficacy through a glimpse at some selected results. The Methodological Mechanism, presented and analyzed in this paper, proved to be useful for diverse types of the research and development activities, including shaping the core definitions, the educational methodological development; course design; structural development of an e-learning platform, and others. Developed for a specific project, Methodological Mechanism might be useful to other emerging projects and initiatives in the field of heritage education and CCH education for the general public and experts in other areas.